A Rare Odontogenic Tumor Known as Cementoblastoma; A Case Report - M Jolehar; M khalili; F baghaii (Islamic Azad University, 2016)
Background: Odontogenic tumors are derived from the epithelial and/or mesenchymal remnants of the tooth-forming apparatus. Therefore, they are found exclusively in tooth-bearing areas. Similar to other neoplasms in the body, odontogenic tumors tend to histologically mimic the cell or tissue of origin. Case history: A 5-year-old boy presented with a chief complaint of pain in the mandible which started 3 months ago. Oral examination revealed bony expansion and a radiopaque mass fused with the roots of deciduous second molar was detected during radiographic examination. After surgical excision of the lesion and the involved tooth, microscopic examination revealed neoplastic tissue consisted of trabeculae of mineralized material with irregular lacunae and prominent basophilic reversal lines. Each trabecula was lined by prominent cells surrounded by cellular connective tissue. The lesion infiltrated the pulp chamber and root canals. Conclusions: According to the clinical and radiographic findings, bone-producing tumors, odontogenic tumors with calcifications and reactive lesions were included in the differential diagnosis. However, based on histopathology and radiographic data, final diagnosis of Cementoblastoma, a benign odontogenic tumor, was confirmed. Patient follow-up revealed no recurrence of the lesion.